Kepastian Hukum Perkawinan Beda Negara Berdasarkan Hukum Perdata Internasional Indonesia - Ervina Martha Herawati; Vonny Fatikha Azzahra; Sheilla Syafadita; Putriana Budhi Pinasty; Farrel Arrigo (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Marriage from a legal perspective is an agreement or agreement that results in the obligations and rights of the man as husband and the woman as wife. Marriage in Indonesia is regulated by law, namely Law Number 1 of 1974 concerning Marriage. The Marriage Law explains several aspects that are closely related to marriage. Apart from the rights and obligations of husband and wife, this regulation also regulates the citizenship and legal status of children resulting from the marriage. The existence of differences in legal regulations in various countries can create potential conflicts and legal uncertainty, especially for couples from different jurisdictions, because it is difficult to know the legal framework that applies to their marriage. This research uses a normative juridical method with a case study of divorce between Indonesian citizens and Japanese foreigners, where the settlement must be carried out in Indonesia. Principles in Private International Law (HPI) emphasize that if a problem is related to the legal aspects or consequences of a legal action, then the legal aspects and consequences must be in accordance with the law in force in the place where the action is carried out in accordance with Article 18AB.